Fumo por lazer, sim!: significados e representações do uso recreativo de maconha para mulheres - Letícia Mara Pereira de Sousa (2020)
Women are increasingly looking to reaffirm their identities and their space in society in the face of the historical construction of invisibility and submission. The differentiation of individuals by gender has a social character and establishes power relations, bringing inequality between them. The gender relationship goes through the subjective and psychosocial aspects experienced by women in all their areas of life, most of the time, in a negative way. Part of these differences is reflected in leisure. The available time, the activities carried out, their meaning and the concept of leisure are different for men and women. In view of gender specificities, this paper discusses the recreational use of marijuana by women today, with the objective of identifying the meaning of this use for them at leisure and understanding the relationship between the representation of women and the use of marijuana . To develop the study, a social survey was conducted through semi-structured interviews. The interviews were conducted in person at the location chosen by the participants, recorded on audio and later fully transcribed. Eight women aged over 18 years, living in Belo Horizonte-MG, were interviewed, who self-declared to use marijuana during leisure time. The women in the research were accessed using the Snowball sampling method. After reading the transcripts, the data were systematized into categories of meaning. For the analysis of the categories, content analysis was used in order to understand what was behind the manifest content, the subjective meanings and the uniqueness of each woman. From the collection and analysis of data, the following categories of meanings attributed to the use of marijuana by women were defined: sociability, affective relationships and sex with marijuana use; relaxation and rest; 'Soothing' and medicine; self-knowledge, identity affirmation and creativity. According to research findings, it was identified that marijuana is inserted in the female universe as a constituent part of the culture and identity of women. Cannabis represents a tool that helps women to be in a psychic state that enables them to enjoy leisure effectively, without crossing social charges. Marijuana, throughout the research, presented itself for women as a signifier of female liberation; the authorization to 'be a woman' as they believe they should be, without the sociocultural judgment, stigmatized and prejudiced that is placed for them. From the understanding of the importance of a (re)construction of identity, we must value the attempt to redefine what women are for themselves and reflect on the place of this body in social space. Marijuana represents a facilitator, a means for these women to reach states, moments of well-being and / or connection with desired feelings, with themselves and / or with other people.